A Study on the Practical Pathways of Integrating Bronze Culture into Ideological and Political Education: A Case Study Based on Baoji’s Bronze Culture - Ma, Xiaoru; Wang, Jinze (Journal of Educational Research and Policies, 2026)
As a significant component embodying the subjectivity of China’s fine traditional culture, bronze culture possesses not only unique artistic value but also represents the crystallization of Chinese wisdom accumulated over millennia. In the context of ideological and political education (IPE) in higher education institutions in the new era, integrating bronze culture into IPE courses is not merely an act of inheriting and promoting traditional culture, but also an innovative expansion of both content and pedagogical approaches in IPE. Currently, cultivating students’ correct value orientations constitutes the core task of IPE in fulfilling its fundamental mission of “moral and intellectual cultivation.” The integration of bronze culture into university IPE represents a practical attempt to combine China’s outstanding traditional culture with modern curricula. Addressing challenges such as the erosion of national cultural subjectivity by erroneous ideological trends, the impact of contemporary social issues on students’ worldviews, and the transformative effects of digital information technologies on IPE, this study proposes concrete integration strategies—namely, developing mobile “Bronze Culture +” IPE classrooms, deeply excavating bronze cultural resources, and innovating teaching models. These measures aim to effectively incorporate Baoji’s bronze culture into university IPE, gradually strengthen college students’ cultural confidence, consolidate foundational values, unite hearts and minds, support the construction of a socialist cultural power, and ensure the continued development of Baoji’s bronze heritage. University IPE must adopt a broad vision, strategic perspective, and profound wisdom by integrating bronze cultural resources into teaching practices. This approach not only advances the transmission of bronze culture but also guides students to enhance cultural confidence and deepen their sense of national belonging. By synthesizing theory with practice, classroom instruction with extracurricular activities, campus life with societal engagement, and historical awareness with present-day realities and future aspirations, educators can deliver a “great ideological and political course” that effectively bridges the “last mile” of IPE.